2021
DOI: 10.1186/s12935-021-02380-2
|View full text |Cite
|
Sign up to set email alerts
|

ITGB1-DT/ARNTL2 axis may be a novel biomarker in lung adenocarcinoma: a bioinformatics analysis and experimental validation

Abstract: Background Lung cancer is one of the most lethal malignant tumors that endangers human health. Lung adenocarcinoma (LUAD) has increased dramatically in recent decades, accounting for nearly 40% of all lung cancer cases. Increasing evidence points to the importance of the competitive endogenous RNA (ceRNA) intrinsic mechanism in various human cancers. However, behavioral characteristics of the ceRNA network in lung adenocarcinoma need further study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…ITGB1-DT was associated with T stage, treatment effect, DSS, and PFI and was an independent risk factor for poor prognosis, suggesting that ITGB1-DT could be a prognostic biomarker for STAD. I T G B 1 -D T p l a y s a n i m p o r t a n t r o l e i n l u n g adenocarcinoma, and it has been reported that interference with ITGB1-DT induces the growth and migration of lung adenocarcinoma cells (8,9). Using the GO analysis, we found that interference with ITGB1-DT expression was related to cell growth.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…ITGB1-DT was associated with T stage, treatment effect, DSS, and PFI and was an independent risk factor for poor prognosis, suggesting that ITGB1-DT could be a prognostic biomarker for STAD. I T G B 1 -D T p l a y s a n i m p o r t a n t r o l e i n l u n g adenocarcinoma, and it has been reported that interference with ITGB1-DT induces the growth and migration of lung adenocarcinoma cells (8,9). Using the GO analysis, we found that interference with ITGB1-DT expression was related to cell growth.…”
Section: Discussionmentioning
confidence: 78%
“…The ITGB1-DT/ITGB1/ Wnt/β-catenin/MYC positive feedback loop was involved in lung adenocarcinoma progression (8). ITGB1-DT/ ARNTL2 promoted the growth and migration of lung adenocarcinoma cells, whereas miR-30b-3p reversed ITGB1/ARNTL2-mediated carcinogenesis (9). Currently, the mechanism of ITGB1-DT in STAD has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…etc. In our previous study, bioinformatics analysis showed that the ITGB1-DT/ARNTL2 axis induces lung adenocarcinoma progression [ 60 ], suggesting the important role of bioinformatics. Moreover, the application of bioinformatic analysis can enhance our understanding of research at the molecular level [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrins were α/β heterodimeric cell surface receptors that play a key role in cell adhesion ( 16 ) and migration ( 17 , 18 ) as well as growth and survival ( 19 , 20 ). The beta-1 subfamily includes 12 unique integrin proteins that bind different extracellular matrix molecules, control extracellular integrin binding, and affect cell adhesion or migration ( 21 , 22 ). Meanwhile, intracellular signal transduction information transcribed from the cytoplasmic tail domain of beta-1 cells contributes to the regulation of cell proliferation ( 23 , 24 ), cytoskeletal reorganization, and gene expression ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%